Ethnobotanical Study of Sengkineh Cultural Tradition in Keruak District, East Lombok Regency - Sp. Ridha Titiani Fitri Al-idrus; Sukiman Sukiman; Kurniasih Sukenti (Jurnal Biologi Tropis, 2021)
Sengkineh is a seven-month cultural tradition since pregnancy, a coastal cultural tradition originating from Sulawesi that passed down from generation to generation. Three ethnic descendants carry out this tradition in the coastal area of Keruak District, namely Mandar, Bugis, and Bajo tribes. The rule consists of three rituals stages: throwing reinforcements into the sea, attaching a necklace to the stomach, and putting the bantang as a sign that they have followed or undergone the ritual. This tradition uses plant resources during its rituals. This study aims to determine the types of plants used in Sengkineh tradition in the Keruak District, East Lombok Regency, related to the plants used and the socio-cultural aspects of the tradition. It is hoped that the results of this research can become a reference for efforts to conserve natural and cultural resources, especially the types of plants used in Sengkineh tradition. This research is a descriptive exploratory survey that was conducted in August - September 2020 in Keruak District, East Lombok Regency. Data collection was carried out through interviews, participatory observation and documentation. Selection of respondents used purposive sampling and snowball sampling (non-discriminative snowball) methods. Data were analyzed descriptively and quantitatively, based on the calculation of Reported Use (RU) and Index of Cultural Significance (ICS). Based on the results obtained, 19 species of plants belong to 12 families and 17 genera used in Sengkineh tradition in Keruak District, East Lombok Regency. Plant species are dominated by Poaceae and Arecaceae which involves three species each. There are four use categories in Sengkineh tradition: offerings, ritual equipment, food ingredients, and secondary materials.